Feelings of being alive - Fingerhut, Jörg; Marienberg, Sabine (de Gruyter, 2012)
This volume brings together texts that originate in various disciplines which examine the feeling of being alive. The focus is on issues of philosophy ofmind and of anthropology, on the theory of emotion, psychology and history of art. The feeling of experience is to be understood as a fundamental, undirected experience of being alive which can be integrated both in a nature-based theory of the organism and in theories of the specific constitution of human experience
Beitr. teilw. engl., teilw. dt. - Zsfassungen in engl. Sprache
Keywords: Konferenzschrift -- 2010 -- Berlin; Philosophische Anthropologie; Gefühl; Existenzphilosophie